The Right to Education between International Obligations and the Challenges of Global Epidemics (Covid 19 Model) - Ftissi, Fouzia (Journal of Legal Studies and Researches, 2023)
This study aims to address the right to education, which despite its importance as a human right and the obligations of states in this regard, faced many legal, human, technical and financing challenges that prevented its implementation and ensuring its enjoyment at the time of Covid 19 as required internationally, despite the efforts made to do so.